Poor Male Students’ Enrolment into Home Economics and Related Programmes in Tertiary Institutions in Anambra State, Nigeria - Ebele Cynthia Emeka; Patricia Ayaegbunem Okoh (International Journal of Home Economics, Hospitality and Allied Research)
The study looked at the issue of poor male students’ enrollment into Home Economics and related programmes in tertiary institutions in Anambra State, Nigeria. It adopted a descriptive survey research design. The population for this study comprised of all the (regular) undergraduate students in the Home Economics related programmes in the five tertiary institutions in Anambra State. The population is two hundred and six (206) students. Instrument used for the study was a structured 4-point questionnaire. The instrument's validity was ensured through consulting experts in Home Economics and Measurement and Evaluation fields in, Nwafor Orizu College of Education, Nsugbe. The reliability of the instrument was established through a test re-test procedure and correlated to yield a coefficient of 0.81. Data for this study was collected primarily by the researchers. The data were analyzed with arithmetic mean and standard deviation. From the results, it was identified that the causes of poor male student enrollment revolve around societal stereotypes, limited awareness of the subject’s scope, inadequate promotional efforts; among others. Educational outreach and awareness, deconstructing gender stereotypes, parental and community engagement, were suggested as strategies to improve male students enrolment. Based on findings, the researchers recommend a curriculum adjustment and more inclusive educational environment and mindset that will showcase Home Economics as a field suitable for all, regardless of gender.